Evaluation of Anti-Helicobacter pylori IgG in Sera of Pregnant Women - Alash, Samir Abdul Amir Abid Ali (Al-Nahrain Journal of Science, 2018)
Helicobacter pylori is a bacterial infection of the stomach, which plays a major role in abdominal symptoms and gastroduodenal pathology. The pregnant women had a significantly higher relative risk of acquiring H.pylori infection during pregnancy as a result of physiological alterations. To investigate the relationship of H.pylori with dyspeptic symptoms in early and late pregnancy, thirty sera samples were obtained from pregnant women and thirty sera samples were obtained from apparently healthy women as control. All studied groups were evaluated anti-Helicobacter pylori IgG antibody by ELISA. Ten of pregnant women samples (33.3%) were seropositive of anti-H. pylori IgG antibody in pregnant women compared with control. This lead to suggest that H. pylori positive may be related to nausea and vomiting in pregnant women.